Exploring Gen-Z Online Fashion Purchase Intention Using SOR Model: The Moderating Role of Gender - Lady, Lady; Shevia, Shevia; Melsen, Fandion; Purwianti, Lily; Liu, ChangBo (Universitas Muhammadiyah Yogyakarta, 2025)
Research aims: This study aimed to investigate Gen-Z online fashion purchase intention in Indonesia using the Stimulus-Organism-Response (SOR) model. In this model, social media marketing (SMM), electronic word-of-mouth (e-WoM), trust, and price served as stimuli, brand image (BI) functioned as the organism, and purchase intention (PI) represented the response, with gender acting as a moderating variable.Design/Methodology/Approach: A causal-comparative research design was used, collecting data from 384 Gen-Z respondents through structured questionnaires. Data analysis was conducted using SmartPLS 4.0, involving measurement model testing for validity and reliability, followed by structural model testing to evaluate path coefficients and hypothesis testing.Research findings: The results showed that trust, e-WoM, and SMM positively influenced PI, both directly and through BI mediation. Gender significantly moderated the effects of e-WoM and SMM on BI but did not affect the influence of trust or price. Furthermore, price showed no significant impact on PI, either directly or through BI mediation, confirming that non-price factors played a greater role in brand perception and purchase behavior among Gen-Z consumers.Theoretical Contribution/Originality: This study integrated BI as a mediating factor within the SOR model, providing deeper insights into Gen-Z brand perception in Indonesia's digital market. The incorporation of gender as a moderating variable showed distinct consumers responses to e-WoM and SMM, challenging the conventional role of price in brand engagement and PI formation.Practitioners/Policy Implications: Online fashion retailers targeting Gen-Z in Indonesia should prioritize trust-building, positive reviews, and authentic social media engagement to strengthen BI and PI. Given price’s limited influence, brands should focus on product quality, experience, and long-term value. Gender-sensitive strategies were also essential, as women responded to relational engagement, while men preferred direct, information-driven content.Research Limitations/Implications: The limitations of this study included a small sample size that might not capture the full range of Indonesian Gen-Z preferences, an exclusive focus on Gen-Z limiting broader applicability, and ambiguous gender effects. Therefore, future studies were recommended to explore technology, influencer marketing, and utilize qualitative methods for deeper insights.